Extracellular Vesicles: Catching the Light in Zebrafish. Issue 10 (October 2019) - Verweij, Frederik J.; Hyenne, Vincent; Van Niel, Guillaume; Goetz, Jacky G.
Abstract : Extracellular vesicles (EVs) circulate in the body fluids of all organisms where they participate in intercellular cross-organ communication. Tracking and understanding these nanosized objects has been hampered by the low resolution of imaging techniques and by the lack of appropriate animal models. The use of zebrafish embryos permits visualization of EVs at unprecedented spatiotemporal resolution using light and electron microscopy. This enables the study of endogenous physiological EVs and pathological EVs side by side, and further unravels their mechanisms of biogenesis, biodistribution, and target cells throughout the organism. These developments will contribute to a better understanding of the in vivo (patho)physiology of EVs. Highlights: Multiple lines of evidence indicate that circulating EVs are involved in cell–cell communication in physiological and pathological contexts. Although their cell biology is now better understood in vitro, how they behave at a subcellular level in complex organisms has remained difficult to assess owing to the lack of animal models adapted to the small size of EVs. Zebrafish embryos allow the visualization of circulating EVs from their cells of origin to their target cells, and permit further exploration of their fate and function during development or tumor progression. In the future, zebrafish systems will certainly contribute to expanding our knowledge on EVs at the whole-organism level.